2010
DOI: 10.1111/j.1525-1594.2010.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile Flow Improves Cerebral Blood Flow in Pediatric Cardiopulmonary Bypass

Abstract: The objective of this study was to evaluate the effect of pulsatile flow on cerebral blood flow (CBF) in infants with the use of a mild hypothermic cardiopulmonary bypass (CPB). Thirty infants scheduled for open heart surgery were randomized to the pulsatile group (Group P, n = 15) and nonpulsatile group (Group NP, n = 15). In Group P, pulsatile perfusion was applied during the aortic cross-clamping period, whereas nonpulsatile perfusion was used in Group NP. The systolic peak velocity (Vs), the end of diastol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
(17 reference statements)
1
10
0
Order By: Relevance
“…Studies conducted on the liver show that pulsatile flow sustains total hepatic blood flow more effectively than continuous flow, due to the specific preservation of hepatic arterial and portal venous blood flow (attributed to prevention of hepatic arterial vasoconstriction) 24 . Similar impact was reported in the neurological system, in that lower vascular resistance and higher flow rates were associated with pulsatile versus nonpulsatile flow 23,25 . Studies conducted on the gastrointestinal (GI) system are concerning, where data has shown that continuous flow is significantly more likely to cause GI bleeding than pulsatile flow, with a near ten-fold incidence difference in some cases 26 .…”
Section: Figuresupporting
confidence: 68%
“…Studies conducted on the liver show that pulsatile flow sustains total hepatic blood flow more effectively than continuous flow, due to the specific preservation of hepatic arterial and portal venous blood flow (attributed to prevention of hepatic arterial vasoconstriction) 24 . Similar impact was reported in the neurological system, in that lower vascular resistance and higher flow rates were associated with pulsatile versus nonpulsatile flow 23,25 . Studies conducted on the gastrointestinal (GI) system are concerning, where data has shown that continuous flow is significantly more likely to cause GI bleeding than pulsatile flow, with a near ten-fold incidence difference in some cases 26 .…”
Section: Figuresupporting
confidence: 68%
“…We used TCDs as a measure of increased ICP in this patient, as invasive monitoring of ICP is often impractical in coagulopathic patients with ALF, and the benefit of such monitoring is not proven. Recently, TCDs have been studied in pediatric traumatic brain injury (TBI) (Melo et al 2011 ), neonatal sepsis (Basu et al 2012 ), cardiopulmonary bypass (Wang et al 2010 ) and extracorporeal membrane oxygenation (O’Brien & Hall 2013 ) as a surrogate for cerebral blood flow. Our patient initially exhibited absent diastolic MCA flow, which improved with another day of head cooling, and correlated with an improved clinical exam.…”
Section: Discussionmentioning
confidence: 99%
“…Not only the quantity, but also the quality of these articles generated by this event based on high‐impact factors (average impact factor is greater than 2.7 annually) are also very impressive. Only during the last 2 years' events, topics covered show the clear evidence of the uniqueness and importance of this conference (Table ) .…”
Section: What Is Unique About This Event?mentioning
confidence: 99%